Mozambique and the Construction of the New African State - Alden, Chris. author. aut Link
XXII, 166 p.
Keywords: An original study of the internationally inspired effort to rebuild this war-torn African country. It seeks to understand the role of the international community in constructing a new kind of African state in the aftermath of conflict and socialism. At the heart of the book is the question of sustainability of the post-conflict African state against the backdrop of the multiple legacies of war, socialism, and regional and international intervention upon an enervated Mozambican society.